Carbon nanotube composite powder and method for preparing the same
Patent Information
- Application Number
- CN202510556181.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
但是,碳纳米管浆料是一种碳纳米管悬浮体系,碳纳米管在浆料存储过程中存在沉降和重新团聚的问题,碳纳米管浆料难以长时间稳定保存
[0031](1)碳纳米管复合粉体中碳纳米管被外加剂、间隔粉体材料分隔和黏附,不存在碳纳米管浆料中碳纳米管的沉降和团聚问题,环境温度影响小,能够长期保存,保质期更长,生产、储存和运输更加方便,更适合在建筑材料中应用。
Smart Images

Figure CN123002832A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a carbon nanotube composite powder and its preparation method. Background Technology
[0002] Carbon nanotubes (CNTs) are a new type of nanofiber material with a diameter in the nanometer range (usually less than 50 nanometers) and a length in the micrometer range (usually 2-50 micrometers). They have extremely high aspect ratios and excellent mechanical properties, and have received widespread attention and research in the field of building materials such as concrete, mortar, asphalt mixtures, and coatings in recent years.
[0003] To achieve good dispersion of carbon nanotubes in building materials, a carbon nanotube slurry is typically prepared first using carbon nanotubes, dispersants, and solvents. This slurry is then uniformly mixed with other materials to prepare the building materials. However, carbon nanotube slurry is a suspension system, and carbon nanotubes are prone to sedimentation and re-agglomeration during storage, making it difficult to maintain stability for extended periods. When applied to building materials, the preparation of these slurries is often constrained by subsequent construction conditions and project schedules, resulting in long usage cycles. Furthermore, the storage environment for carbon nanotube slurries is sometimes unsuitable, making practical use difficult and often requiring immediate preparation. Additionally, measures (such as spraying) are necessary to ensure uniform dispersion in building materials, further increasing the difficulty of application. These problems severely hinder the widespread application of carbon nanotubes in building materials.
[0004] Therefore, there is an urgent need to develop a carbon nanotube dispersion system that can be stored for a long time and is easy to use. Summary of the Invention
[0005] In view of the problems existing in the prior art, the present invention provides a carbon nanotube composite powder and its preparation method. The carbon nanotube composite powder includes carbon nanotubes, spacer powder material and additives. The additives disperse the carbon nanotubes, and the spacer powder material separates or adheres the carbon nanotubes. After drying, the carbon nanotubes and spacer powder material are bonded together by the additives into agglomerates. On the one hand, the agglomerates can be redispersed during use, thereby achieving the purpose of good dispersion of carbon nanotubes in the target application material (e.g., building materials) and better exerting the role of carbon nanotubes. On the other hand, the carbon nanotubes exist in solid form as carbon nanotube composite powder, which can not only be stored for a long time, but is also convenient to use.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] One objective of this invention is to provide a carbon nanotube composite powder, comprising carbon nanotubes, spacer powder material, and additives, wherein the carbon nanotubes and spacer powder material are bonded together by the additives into aggregates; in the carbon nanotube composite powder, the mass percentage of carbon nanotubes is 1.0% to 26.0%, for example, 1.0%, 2.0%, 4.0%, 5.0%, 7.0%, 10.0%, 12.0%, 15.0%, 16.0%, 18.0%, 20.0%, 23.0%, 25.0%, or 26.0%, etc., and the mass percentage of additives is 0.2% to 10.0%, for example, 0.2%, 0.5%, 1.0%, 3.0%, 5.0%, 7.0%, 8.0%, or 10.0%, etc.
[0008] The carbon nanotube composite powder of the present invention comprises carbon nanotubes, spacer powder material, and additives. The additives disperse the carbon nanotubes, and the spacer powder material separates or adheres the carbon nanotubes, so that the carbon nanotubes and spacer powder material are bonded together by the additives into agglomerates. On the one hand, the agglomerates can be redispersed during use, thereby achieving the purpose of good dispersion of carbon nanotubes in the target application material (e.g., building materials) and better exerting the role of carbon nanotubes. On the other hand, the carbon nanotubes exist in solid form as carbon nanotube composite powder, which can not only be stored for a long time, but is also convenient to use.
[0009] As a preferred embodiment of the present invention, the carbon nanotube composite powder further includes a supporting powder material for providing a supporting basis for the carbon nanotubes and / or the aggregates; in the carbon nanotube composite powder, the mass ratio of the spacer powder material to the supporting powder material is ≥1:9.
[0010] Preferably, the D of the supported powder material 50 ≤50μm.
[0011] Preferably, the loaded powder material includes any one or a combination of at least two of the following: concrete mineral admixtures, cementitious materials, asphalt mixture fillers, and coating fillers.
[0012] Preferably, the loaded powder material includes any one or a combination of at least two of the following: fly ash, microspheres, granulated blast furnace slag powder, metakaolin, pozzolanic mixture, zeolite powder, cement, titanium dioxide, calcium carbonate, calcium silicate, silicate, diatomite, limestone powder, quartz sand powder, gypsum powder, various rock and waste residue powders, and carbon fiber powder.
[0013] As a preferred technical solution of the present invention, the D of the aggregate 50 ≤500μm, preferably, the D of the aggregates 50 ≤100μm.
[0014] Preferably, the carbon nanotubes include multi-walled carbon nanotubes and / or single-walled carbon nanotubes.
[0015] As a preferred technical solution of the present invention, the spacer powder material D 50 ≤2μm.
[0016] Preferably, the spacer powder material comprises silica fume and / or nano-calcium carbonate.
[0017] It should be noted that silica fume is an ultrafine powder material with amorphous silica as its main component, obtained by collecting silicon vapor discharged through flues during the smelting of ferrosilicon alloys or industrial silicon.
[0018] As a preferred embodiment of the present invention, the additive includes a dispersant.
[0019] Preferably, the dispersant comprises any one or a combination of at least two of the following: sodium dodecylbenzenesulfonate (SDBS), sodium dodecyl sulfate (SDS), sodium dodecyl sulfonate (SLS), hexadecyltrimethylammonium bromide (CTAB), cyclodextrin, gum arabic, polyethylene glycol-polyacrylamide-polystyrene (PEG-PAM-PS), polyvinylpyrrolidone (PVP), concrete water-reducing agent, polyvinyl alcohol, and cellulose ether.
[0020] It should be noted that, in addition to dispersants, admixtures such as defoamers and binders can be selectively added depending on the actual application. These admixtures are used to eliminate bubbles, disperse carbon nanotubes and spacer powder materials, and bind carbon nanotubes and spacer powder materials together to form small aggregates.
[0021] As a preferred embodiment of the present invention, some or all of the carbon nanotubes undergo surface modification treatment.
[0022] Preferably, some or all of the spacer powder material undergoes surface modification treatment.
[0023] It should be noted that by selectively modifying some or all of the carbon nanotubes and spacer powder materials, certain functional effects of carbon nanotube composite powders can be enhanced. For example, carbon nanotube composite powders can exhibit hydrophilicity or hydrophobicity.
[0024] As a preferred technical solution of the present invention, the carbon nanotubes in the carbon nanotube composite powder are all or partly replaced by graphene oxide and / or carbon nanofibers of equal mass, and the mass percentage of the replaced carbon nanotubes is 10% to 100%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 90%, or 100%.
[0025] A second objective of this invention is to provide a method for preparing the carbon nanotube composite powder described in the first objective. The preparation method includes: using a solvent to mix carbon nanotubes, spacer powder material and additives evenly, and then drying and pulverizing the mixture to obtain the carbon nanotube composite powder.
[0026] It should be noted that in the preparation method described in this invention, the solvent is selected according to the solubility of the additive, which can make the carbon nanotubes, spacer powder materials and additives mixed evenly. Moreover, the drying and powdering can be carried out by spray drying or by drying first and then crushing. Those skilled in the art can choose according to the actual situation, which will not be elaborated here.
[0027] As a preferred technical solution of the present invention, the preparation method includes: using a solvent to mix carbon nanotubes, spacer powder materials, supported powder materials and additives evenly, and then drying and pulverizing to obtain the carbon nanotube composite powder.
[0028] As a preferred technical solution of the present invention, the preparation method includes: first, mixing the additive and solvent evenly, then adding carbon nanotubes to form a carbon nanotube slurry, and finally adding spacer powder material and load powder material and mixing evenly, and then drying and pulverizing to obtain the carbon nanotube composite powder.
[0029] Carbon nanotubes, as fiber-reinforced materials, have been researched and applied in many technological fields, such as building materials like concrete, mortar, asphalt mixtures, and coatings, where they have received widespread attention and research. When applying carbon nanotubes in the form of carbon nanotube composite powders, given a fixed amount of carbon nanotubes, the amount of corresponding materials in the raw material formulation can be replaced by adjusting the type and amount of the spacer and load powder materials within the carbon nanotube composite powder.
[0030] Compared with existing technical solutions, the present invention has at least the following beneficial effects:
[0031] (1) In carbon nanotube composite powder, carbon nanotubes are separated and adhered by additives and spacer powder materials. There is no problem of sedimentation and agglomeration of carbon nanotubes in carbon nanotube slurry. The environmental temperature has little impact, it can be stored for a long time, has a longer shelf life, and is more convenient to produce, store and transport, making it more suitable for application in building materials.
[0032] (2) Carbon nanotube composite powder can be pre-prepared as a dry mixture with other dry materials to avoid problems such as inaccurate metering and poor dispersion that may occur when adding carbon nanotube slurry during subsequent stirring, thus simplifying the use process and improving the quality stability of building materials with carbon nanotubes.
[0033] (3) The carbon nanotubes and spacer powder materials in the carbon nanotube composite powder are bonded into small aggregates by additives, which can greatly reduce the problem of carbon nanotubes and fine powder loss during use, and greatly reduce the risk of operators inhaling fine materials, making it safe and environmentally friendly to use.
[0034] (4) Carbon nanotubes and spacer powder materials are bonded together into small aggregates by additives and can be redispersed during use, so as to give full play to the role of carbon nanotubes.
[0035] (5) By surface modification of carbon nanotubes and spacer powder materials, or by adjusting the type of spacer powder materials and additives, carbon nanotube composite powders can exhibit hydrophilic or hydrophobic properties, thus making them suitable for different building material systems such as concrete, mortar, asphalt mixtures, and coatings, with a wide range of applications. Attached Figure Description
[0036] Figure 1 This is a scanning electron microscope image of the macroscopic dispersion state of the carbon nanotube composite powder described in Example 1 of the present invention;
[0037] Figure 2 This is a scanning electron microscope image of an agglomerate with loaded powder material in the carbon nanotube composite powder described in Example 1 of the present invention;
[0038] Figure 3 yes Figure 2 A magnified view of a portion of the image;
[0039] Figure 4 This is a scanning electron microscope image of an agglomerate without loaded powder material in the carbon nanotube composite powder described in Example 1 of the present invention;
[0040] Figure 5 This is a scanning electron microscope image of the carbon nanotube composite powder described in Comparative Example 1 of the present invention;
[0041] Figure 6 This is a scanning electron microscope image of the carbon nanotube composite powder described in Comparative Example 2 of the present invention. Detailed Implementation
[0042] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0043] To better illustrate the present invention and facilitate understanding of its technical solutions, typical but non-limiting embodiments of the present invention are as follows:
[0044] Example 1
[0045] This embodiment provides a carbon nanotube composite powder, which is composed of carbon nanotubes, spacer powder material, supporting powder material, and additives. Specifically, the composition is as follows (by mass percentage): 2.5% multi-walled carbon nanotubes, 0.5% additives, 37.0% silica fume, and 60.0% granulated blast furnace slag powder; wherein the additive is polyvinylpyrrolidone (PVP), and the granulated blast furnace slag powder has a D... 50 It is 19μm; the D of silica fume 50 It is 0.15μm.
[0046] The carbon nanotube composite powder described in this embodiment was prepared using the following method: First, 0.05 kg of additive was dispersed in 13.5 kg of water, then 0.25 kg of carbon nanotubes were added to form a carbon nanotube slurry; then, 3.7 kg of silica fume and 6.0 kg of granulated blast furnace slag powder were gradually added to the carbon nanotube slurry, mixed evenly, and then dried to form the carbon nanotube composite powder; the D of the carbon nanotube composite powder was tested. 50 It is 16μm.
[0047] The scanning electron microscope image of the carbon nanotube composite powder described in this embodiment is as follows: Figures 1-4 As shown, Figure 1 This refers to the macroscopic dispersion state of carbon nanotube composite powders. Figure 2 It targets agglomerates containing loaded powder materials. Figure 3 yes Figure 2 A magnified view of a portion of the image. Figure 4 The target is agglomerates without loaded powder materials. It can be seen that carbon nanotubes (fibrous material in the figure) are separated by silica fume (small spherical particles in the figure). Some carbon nanotubes are also directly adsorbed on granulated blast furnace slag powder (larger particles with irregular shapes in the figure). The carbon nanotubes and the spacer powder materials are bonded together by additives to form small agglomerates with a size in the micrometer range.
[0048] Example 2
[0049] This embodiment provides a carbon nanotube composite powder, which is composed of carbon nanotubes, spacer powder material, load powder material, and additives. Specifically, the composition is as follows (by mass percentage): 2.5% multi-walled carbon nanotubes, 1.0% additives, 36.5% silica fume, and 60.0% limestone powder; wherein the additive is a polycarboxylate superplasticizer, and the limestone powder has a D... 50 It is 15μm; the D of silica fume 50 It is 0.15μm.
[0050] The preparation method of the carbon nanotube composite powder in this embodiment is the same as that in Example 1. The D content of the carbon nanotube composite powder was tested. 50 It is 13μm.
[0051] Example 3
[0052] This embodiment provides a carbon nanotube composite powder, which is composed of carbon nanotubes, spacer powder material, and additives. Specifically, the composition is as follows (by mass percentage): 5.0% multi-walled carbon nanotubes, 1.0% additives, and 94.0% silica fume; wherein the additives consist of 10% organosilicon defoamer and 90% polyvinylpyrrolidone (PVP); the silica fume has a D... 50 It is 0.15μm.
[0053] The preparation method of the carbon nanotube composite powder in this embodiment is the same as that in Example 1. The D content of the carbon nanotube composite powder was tested. 50 It is 10μm.
[0054] Example 4
[0055] This embodiment provides a carbon nanotube composite powder, which is composed of carbon nanotubes, spacer powder material, load powder material, and additives. Specifically, the composition, by mass percentage, is: 0.5% single-walled carbon nanotubes, 0.5% multi-walled carbon nanotubes, 1.0% additives, 38.0% nano-calcium carbonate, 10.0% microspheres, and 50.0% granulated blast furnace slag powder; wherein the additives consist of 70% polyvinylpyrrolidone (PVP), 10% sodium dodecyl sulfate, and 20% polyvinyl alcohol; the nano-calcium carbonate has a D... 50 The microspheres have a diameter of 0.06 μm. 50 The D of granulated blast furnace slag powder is 5μm. 50 It is 19μm.
[0056] The preparation method of the carbon nanotube composite powder in this embodiment is the same as that in Example 1. The D content of the carbon nanotube composite powder was tested. 50 It is 12μm.
[0057] Example 5
[0058] This embodiment provides a carbon nanotube composite powder, which is composed of carbon nanotubes, spacer powder material, and additives. Specifically, the composition is as follows (by mass percentage): multi-walled carbon nanotubes 25.0%, additives 10.0%, silica fume 30.0%, and nano-calcium carbonate 35.0%; wherein the additives consist of 1% organosilicon defoamer, 5% hexadecyltrimethylammonium bromide (CTAB), 70% concrete water-reducing agent, 14% cyclodextrin, and 10% polyvinyl alcohol; the silica fume contains D... 50 The D of nano-calcium carbonate is 0.15 μm. 50 It is 0.06μm.
[0059] The preparation method of the carbon nanotube composite powder in this embodiment is the same as that in Example 1. The D content of the carbon nanotube composite powder was tested. 50 It is 9μm.
[0060] Example 6
[0061] This embodiment provides a carbon nanotube composite powder, which is composed of carbon nanotubes, spacer powder material, load powder material, and additives. Specifically, the composition, by mass percentage, is: 2.5% multi-walled carbon nanotubes, 1.5% additives, 36.0% silica fume, 5.0% metakaolin, 5.0% diatomaceous earth, 20.0% fly ash, 10.0% microspheres, and 20.0% limestone powder. The additives consist of 5% sodium dodecylbenzenesulfonate (SDBS), 25% polyethylene glycol-polyacrylamide-polystyrene (PEG-PAM-PS), 35% polyvinylpyrrolidone (PVP), 10% gum arabic, and 25% polyvinyl alcohol. The silica fume contains D... 50 The D of kaolinite is 0.15 μm. 50 The D of diatomaceous earth is 21 μm. 50 The density of fly ash is 8 μm. 50 The microspheres have a diameter of 16 μm and a density of 16 μm. 50 The density of limestone powder is 5 μm. 50 It is 15μm.
[0062] The preparation method of the carbon nanotube composite powder in this embodiment is the same as that in Example 1. The D content of the carbon nanotube composite powder was tested. 50 It is 13μm.
[0063] Comparative Example 1
[0064] This comparative example provides a carbon nanotube composite powder, which differs from Example 1 only in that: the specific composition of the carbon nanotube composite powder is: by mass percentage, 2.5% multi-walled carbon nanotubes, 37.5% silica fume, and 60.0% granulated blast furnace slag powder; that is, the additives are omitted.
[0065] The preparation method of the carbon nanotube composite powder in this comparative example is the same as that in Example 1. However, due to the lack of a dispersant, the carbon nanotubes are poorly dispersed, and there are many carbon nanotube agglomerates in the carbon nanotube composite powder. The relevant scanning electron microscope images are shown below. Figure 5 As shown.
[0066] Comparative Example 2
[0067] This comparative example provides a carbon nanotube composite powder, which differs from Example 1 only in that: the specific composition of the carbon nanotube composite powder is: by mass percentage, 2.5% multi-walled carbon nanotubes, 0.5% additives, and 97.0% granulated blast furnace slag powder; that is, the spacer powder material (silica fume) is omitted.
[0068] The preparation method of the carbon nanotube composite powder in this comparative example is the same as that in Example 1. However, due to the lack of silica fume separation, a large number of carbon nanotubes agglomerated during the drying process, resulting in a large number of carbon nanotube agglomerates in the carbon nanotube composite powder. Relevant scanning electron microscope images are shown below. Figure 6 As shown.
[0069] The composite powders from the above examples and comparative examples were used in ultra-high performance concrete to test their reinforcing effect. The mix proportions of the ultra-high performance concrete foundation are shown in Table 1 (unit: kg / m³). 3 According to the principle that carbon nanotubes account for 0.05% of the mass of the cementitious material, the composite powders of the above-mentioned examples and comparative examples were added respectively. Furthermore, based on the type and amount of the spacer powder material and the supporting powder material in the carbon nanotube composite powder, the corresponding materials in the basic ratio of Representative 1 were added. The mixing ratios are shown in Table 2 (unit: kg / m³). 3 ).
[0070] Table 1
[0071]
[0072]
[0073] Table 2
[0074]
[0075] According to the proportions in Tables 1 and 2, all raw materials except water are first mixed into a dry mixture using a mixer. Then, the dry mixture and water are mixed evenly using a mixer. Standard specimens are then formed, steam-cured, and tested for their 7-day compressive strength, axial tensile strength, and flexural strength. The mechanical properties of ultra-high performance concrete are shown in Table 3.
[0076] Table 3
[0077]
[0078]
[0079] As shown in Table 3, the addition of the carbon nanotube composite powder proposed in this invention (Examples 1-6) to ultra-high performance concrete can significantly improve the axial tensile strength and flexural strength of ultra-high performance concrete, and slightly increase the compressive strength. However, when using Comparative Example 1 (without admixture) and Comparative Example 2 (without silica fume), due to the lack of the dispersing effect of admixture and the lack of the separating effect of silica fume, the carbon nanotubes re-agglomerate during the drying process, which significantly reduces their reinforcing effect and even produces a negative effect (Comparative Example 2).
[0080] In summary, the carbon nanotube composite powder of the present invention comprises carbon nanotubes, spacer powder material, and additives. The additives disperse the carbon nanotubes, and the spacer powder material separates or adheres the carbon nanotubes, so that the carbon nanotubes and spacer powder material are bonded together by the additives into aggregates. On the one hand, the aggregates can be redispersed during use, thereby achieving the purpose of good dispersion of carbon nanotubes in the target application material (e.g., building materials) and better exerting the role of carbon nanotubes. On the other hand, the carbon nanotubes exist in solid form as carbon nanotube composite powder, which can not only be stored for a long time, but is also convenient to use.
[0081] The present invention has been illustrated with detailed structural features through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvements to the present invention fall within the protection and disclosure scope of the present invention.
[0082] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0083] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0084] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A carbon nanotube composite powder, characterized in that, The carbon nanotube composite powder comprises carbon nanotubes, spacer powder material, and additives. The carbon nanotubes and spacer powder material are bonded together by the additives into aggregates. In the carbon nanotube composite powder, the mass percentage of carbon nanotubes is 1.0% to 26.0%, and the mass percentage of additives is 0.2% to 10.0%.
2. The carbon nanotube composite powder according to claim 1, characterized in that, The carbon nanotube composite powder further includes a supporting powder material for providing a supporting basis for the carbon nanotubes and / or the aggregates; in the carbon nanotube composite powder, the mass ratio of the spacer powder material to the supporting powder material is ≥1:
9. Preferably, the D of the supported powder material 50 ≤50μm; Preferably, the loaded powder material includes any one or a combination of at least two of the following: concrete mineral admixtures, cementitious materials, asphalt mixture fillers, and coating fillers; Preferably, the loaded powder material includes any one or a combination of at least two of the following: fly ash, microspheres, granulated blast furnace slag powder, metakaolin, pozzolanic mixture, zeolite powder, cement, titanium dioxide, calcium carbonate, calcium silicate, silicate, diatomite, limestone powder, quartz sand powder, gypsum powder, various rock and waste residue powders, and carbon fiber powder.
3. The carbon nanotube composite powder according to claim 1 or 2, characterized in that, The aggregate D 50 ≤500μm, preferably, the D of the aggregates 50 ≤100μm. Preferably, the carbon nanotubes include multi-walled carbon nanotubes and / or single-walled carbon nanotubes.
4. The carbon nanotube composite powder according to claim 1 or 2, characterized in that, The spacer powder material D 50 ≤2μm; Preferably, the spacer powder material comprises silica fume and / or nano-calcium carbonate.
5. The carbon nanotube composite powder according to claim 1 or 2, characterized in that, The additives include dispersants; Preferably, the dispersant comprises any one or a combination of at least two of the following: sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, cyclodextrin, gum arabic, polyethylene glycol-polyacrylamide-polystyrene, polyvinylpyrrolidone, concrete water-reducing agent, polyvinyl alcohol, and cellulose ether.
6. The carbon nanotube composite powder according to claim 1 or 2, characterized in that, Some or all of the carbon nanotubes have undergone surface modification treatment; Preferably, some or all of the spacer powder material undergoes surface modification treatment.
7. The carbon nanotube composite powder according to claim 1 or 2, characterized in that, The carbon nanotubes in the carbon nanotube composite powder are all or partly replaced by graphene oxide and / or carbon nanofibers of equal mass.
8. A method for preparing carbon nanotube composite powder according to any one of claims 1-7, characterized in that, The preparation method includes: using a solvent to mix carbon nanotubes, spacer powder materials and additives evenly, and then drying and pulverizing them to obtain the carbon nanotube composite powder.
9. The preparation method according to claim 8, characterized in that, The preparation method includes: using a solvent to mix carbon nanotubes, spacer powder materials, supported powder materials and additives evenly, and then drying and pulverizing to obtain the carbon nanotube composite powder.
10. The preparation method according to claim 9, characterized in that, The preparation method includes: first, mixing the additive and solvent evenly, then adding carbon nanotubes to form a carbon nanotube slurry, and finally adding spacer powder and load powder materials and mixing evenly, followed by drying and powdering to obtain the carbon nanotube composite powder.
